Management practices as antecedents of safety culture within the trucking industry: similarities and differences by hierarchical level (2008)
Problem: A homogeneous perception of safety is important for the achievement of a strong safety culture; however, employees may differ in their safety perceptions, depending on their position and/or hierarchical level within the organization. Moreover, there is limited information on the antecedents of safety culture. This study examines how safety training, driver scheduling autonomy, opportunity for safety input, and management commitment to safety influence individuals' perceptions of safety culture. Method: Data for this study were drawn from 116 trucking firms, stratified by three safety performance levels. The data were collected from drivers (lowest hierarchical level), dispatchers (medium hierarchical level), and safety directors (highest hierarchical level), regarding their perceptions of their respective corporate safety cultures.